Pursuing the Goal of Sustainable Action in the Basic Training of Teachers. (20th July 2016) - Varela-Losada, Mercedes; Álvarez-Lires, Xabier; Lorenzo-Rial, María; Pérez-Rodríguez, Uxío
Abstract: School can and should promote the development of sustainable lifestyles that lead communities to be fairer and more responsible and respectful with the environment and people. Thus, Environmental Education must focus on the development of a competence for action based on critical thinking, independent decision-making and participation. The objective of this study is to analyse if teachers in pre-service training are aware of the main purpose Environmental Education must pursue and what this implies. The research was carried out via mixed methodology, contrasting the data obtained through a Likert scale of attitudes with other qualitative data. The analysis of the data suggests the existence of future teachers' frequent predisposition to believing that the essential aim should simply be an awareness of environmental problems, perpetuating in this way the gap that separates the daily educational practice of the current environmental philosophy.